Transport of glutathione, as gamma-glutamylcysteinylglycyl ester, into liver and kidney. - Puri, R N (1983)
Administration of gamma-glutamylcysteinylglycyl monomethyl (or monoethyl) ester to mice leads to substantial increases in the levels of glutathione in the liver and kidney. Mice depleted of glutathione by treatment with buthionine sulfoximine, a potent inhibitor of gamma-glutamylcysteine synthetase, exhibited about a 4-fold increase in liver and kidney glutathione levels after administration of glutathione monomethyl ester. This ester also prevented the marked decline in liver glutathione level found after giving mice acetaminophen, and it protected mice from toxicity due to this compound. The findings indicate that the monomethyl and monoethyl esters of glutathione are transported into cells and hydrolyzed to glutathione. Such esters may be useful in experimental work on glutathione metabolism and function and may provide a relatively safe method for protecting cells against damage by toxic compounds, oxygen, and radiation.